2018
DOI: 10.1111/epi.14486
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous brivaracetam in status epilepticus: A retrospective single‐center study

Abstract: Brivaracetam (BRV) is a high-affinity synaptic vesicle glycoprotein 2A ligand that is structurally related to levetiracetam (LEV). Compared to LEV, its affinity to the ligand is >10%-30% higher. Due to its more lipophilic characteristics, it might have a quicker penetration across the blood-brain barrier and potentially also a stronger anticonvulsant effect. Thus, we aimed to explore its usefulness in the treatment of status epilepticus (SE). We retrospectively assessed treatment response and adverse events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
6
36
0
2
Order By: Relevance
“…The corrected half‐times for 100 mg BRV and 1500 mg LEV in this clinical study are similar to the 3‐minute and 23‐ minute half‐times observed in the nonhuman primate study at doses intended to result in equivalent plasma levels in humans. Despite neither BRV nor LEV being indicated for SE, recent studies have suggested that SE patients can be treated with BRV, with loading doses similar to those in this study . A further recent study has reported that a human dose of at least 2 mg/kg and up to 5 mg/kg is necessary for efficacy in SE, suggesting that doses slightly above 100 mg BRV intravenously could be in the efficacious range .…”
Section: Discussionsupporting
confidence: 56%
“…The corrected half‐times for 100 mg BRV and 1500 mg LEV in this clinical study are similar to the 3‐minute and 23‐ minute half‐times observed in the nonhuman primate study at doses intended to result in equivalent plasma levels in humans. Despite neither BRV nor LEV being indicated for SE, recent studies have suggested that SE patients can be treated with BRV, with loading doses similar to those in this study . A further recent study has reported that a human dose of at least 2 mg/kg and up to 5 mg/kg is necessary for efficacy in SE, suggesting that doses slightly above 100 mg BRV intravenously could be in the efficacious range .…”
Section: Discussionsupporting
confidence: 56%
“…(mRS) scores at admission and discharge, and in responders and nonresponders to topiramate (TPM) [41][42][43] Two recent case series reported on the use of oral perampanel in patients with various stages of SE, reporting response rates between 17% 44 and 37%. 45 Use of oral oxcarbazepine in SE was reported in 13 patients with a median treatment latency of 81 hours.…”
Section: F I G U R E 2 Modified Rankin Scalementioning
confidence: 99%
“…Despite availability of animal studies showing potential benefits of BRV in treatment of SE, clinical evidence in SE is limited . Two clinical studies were identified (Table ) . A retrospective chart review was conducted of patients who had received BRV for SE.…”
Section: Discussionmentioning
confidence: 99%
“…No serious adverse effects were reported. Authors noted that BRV responders were treated earlier in the course of their SE compared with BRV nonresponders …”
Section: Discussionmentioning
confidence: 99%